Stakeholder Involvement and Team Capacity on the Performance of Rural Electrification Projects in Southwestern Uganda - Violah Mpangwire; Sarah Ainomugisha; Benjamin Musiita (Journal of Economics and Behavioral Studies, 2024)
This research delves into the dynamics of stakeholder involvement and team capacity in shaping the success of rural electrification projects in Southwestern Uganda. The study adopted a cross-sectional design using a quantitative approach. Data was collected from a population of 38 rural electrification projects in Southwestern Uganda. A sample of 34 projects was determined using Krejicie and Morgan's Table 1970, and these were selected through simple random sampling. Findings indicate significant positive relationships between stakeholder involvement, team capacity, and project performance. The analysis reveals that 41.9% of the variations in project performance are explained by stakeholder involvement and team capacity, with 58.1% unaccounted for, signaling potential avenues for future research. The study concludes by advocating for strategic interventions that prioritize stakeholder engagement and team capacity in rural electrification projects in Southwestern Uganda. Therefore, it is important to emphasize the critical role of engaging stakeholders and enhancing team capabilities for successful rural electrification projects.